Immediate effects of Global Active Stretching on strength and flexibility: Randomised controlled trial - Rodrigues, Elisa (2024)
Global Active Stretching is a relatively recent yet little studied stretching method. It differs from the most popular methods by targeting muscle chains and integrating stretching with muscle contractions, which may eventually avoid the post-stretching reduction of strength that occurs in other methods. To verify the immediate effects of Global Active Stretching on muscle strength and flexibility in individuals with short hamstrings. A single-blind randomised controlled trial was carried out on 30 volunteers with more than 20° in the active knee extension test, randomly assigned to three groups: the experimental group (Global Active Stretching exercise); the placebo group (Global Active Stretching initial position without stretching); and the control group (lying down). The active knee extension and fingertip-to-floor tests assessed hamstring and posterior chain flexibility. Hamstring and quadriceps strength were assessed using the peak torque evaluation in the Biodex System 4PRO®. Assessments took place before and immediately after the 15-minute intervention. The ANOVA and the paired t test were used (α = 0.05). The experimental group had a significant increase in flexibility in both the fingertip-to-floor test (8.3 cm) and the active knee extension test (6.3°) when compared to the placebo and control groups (p < 0.05), while no differences in strength were observed (p > 0.05). Global Active Stretching immediately increased hamstring flexibility without significantly reducing muscle strength. Thus, individuals seeking to enhance their short-term flexibility can benefit from this programme in a single session without compromising performance.